2005
DOI: 10.1093/annonc/mdi358
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine pancreatic tumors: factors correlated with survival

Abstract: Tumor resection, the absence of liver and lymph node metastases, and the presence of MEN 1 syndrome are related to a better survival rate. Radical surgery continues to have a central role in the therapeutic approach to endocrine tumors of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(99 citation statements)
references
References 22 publications
9
85
2
2
Order By: Relevance
“…The study was performed with the aim of deciphering alterations potentially related to the progression of this disease, and of providing a source of possible biomarkers and/or molecular targets. The characteristics of our samples (Ki-67 >2, primary size !3 cm), together with the presence of liver metastases and the progression of disease in each single patient, were all known to be predictive of poor prognosis , Tomassetti et al 2005, with both biotherapy and chemotherapy being poorly effective (O'Toole et al 2004, Oberg & Eriksson 2005, as confirmed by the outcome of five of the seven patients we have had under care in the follow-up period.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The study was performed with the aim of deciphering alterations potentially related to the progression of this disease, and of providing a source of possible biomarkers and/or molecular targets. The characteristics of our samples (Ki-67 >2, primary size !3 cm), together with the presence of liver metastases and the progression of disease in each single patient, were all known to be predictive of poor prognosis , Tomassetti et al 2005, with both biotherapy and chemotherapy being poorly effective (O'Toole et al 2004, Oberg & Eriksson 2005, as confirmed by the outcome of five of the seven patients we have had under care in the follow-up period.…”
Section: Discussionmentioning
confidence: 61%
“…Although considered to be 'indolent' tumours, at the time of diagnosis almost two-thirds of NF PETs present with liver metastases, which is the main factor determining the patients' outcome , Tomassetti et al 2005). In addition, the different spontaneous behaviour of PETs (stable or progressive disease) plays a crucial role in their natural history.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, differentiation of GEP NET classified as poorly compared with well-differentiated (WD) carcinoma (Johnson et al 1986, Greenberg et al 1987, Madeira et al 1998, Travis et al 1998, Rindi et al 1999, Lim et al 2005, Panzuto et al 2005, Asamura et al 2006, Faggiano et al 2007, Lepage et al 2007, Pape et al 2008 and stage (Lo et al 1996, Pelosi et al 1996, Burke et al 1997, Madeira et al 1998, Kirshbom et al 1999, Rindi et al 1999, Shebani et al 1999, Onaitis et al 2000, Quaedvlieg et al 2001, Rigaud et al 2001, Solorzano et al 2001, Hochwald et al 2002, Plöckinger et al 2004, Panzuto et al 2005, Tomassetti et al 2006, Baudin 2007, Pape et al 2008 as long been recognized the strongest prognostic parameters before the primary location. More recently, lymph node metastases (Hellman et al 2002, Cardillo et al 2004, Lim et al 2005, Tomassetti et al 2005, Baudin 2007, García-Yuste et al 2007, Rea et al 2007, Pape et al 2008 and proliferative index have emerged as major determinant of prognosis in GEP tumors of the lung (Travis et al 1998, Beasley ...…”
Section: Introductionmentioning
confidence: 99%
“…PETs are classified as 'functioning' (F) or 'non-functioning' (NF) depending on the presence or absence of a syndrome due to excessive hormone secretion from cancer cells (Plockinger et al 2004). Although PETs are considered to be 'indolent' tumours, at the time of diagnosis approximately 60% of NF PETs patients have liver metastases, which represent the most important factor determining their outcome , Tomassetti et al 2005. In patients with metastatic, progressive PETs, therapy with somatostatin analogues is poorly effective, with only 27% response .…”
Section: Introductionmentioning
confidence: 99%